PEMANFAATAN MEDIA QR (QUICK RESPONSE) CODE UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS BIOGRAFI OLEH SISWA KELAS X MAS AL-WASHLIYAH KOTA TEBING TINGGI - Wiranda, Wiranda; Hasibuan, Abdullah (Universitas Islam Sumatera Utara, 2023)
This thesis is motivated by increasingly sophisticated tecnological develoments in learning media, it is very important to motivate students in improving writing skills. High school year 2022-2023 and be able to find out what obstacles are faced in using Qr Code learning media to improve the ability to write biographical texts by class X MAS Al-Washliyah Tebing Tinggi City in The 2022-2023 school year.This Type of experimental and survey research methods.The population of this study amounted to 159 students, while the sample of this study amounted 40 students. The result of this study can be seen that from the results of the pre-test (without media) there were 33 students who scored 20-74 and those who scored above the KKM were 7 students with scores between 76-82. While from the results of the post-test (whith the media) student got a score of 74 and 39 other students got a score of 76-94. So this study concluded that the use of QR (Quick Response) Code media to improve the writing ability of class X MAS AL-Washliyah Tebing Tinggi city in the 2022-2023 Academic year, this can be seen from the students writing ability in writing biographical texts according to predetermined criteria, students can understand the language used in writing biographical student write down the superior characters of the characters texts identify aspects.